Tetrahedral meshing by finite element analysis for surface cracks with respect to corner point singularities for smooth and stepped round bars / Sharon Teh Ai Ping - Sharon Teh , Ai Ping (2022)
Numerous failure investigations involving failed round bars for various applications have been reported in literature. The cracks are predominantly initiated at high stress concentration regions. However, in the ensuing failure investigations, the use of numerical fracture mechanics was commonly omitted. The current advancement of computational development on the interactive numerical techniques allows the analysts to more accessibly figure out the fracture phenomena when performing engineering analyses nowadays. The stress intensity factors (SIFs) of a surface planar flaw at a stepped round bar are of practical interest, however, the SIF solutions along the flaw front have not yet been documented in literature. In this study, the practical abilities of the numerical fracture mechanics on the fracture analyses were demonstrated by evaluating a planar surface flaw at the shoulder fillet through numerical simulations by the finite element method (FEM) and the dual boundary element method (DBEM) for both smooth and stepped round bars. Crack front SIFs results from FEM studies have shown corner point singularity issues. The SIF data for relatively small crack sizes are valuable to gauge whether an existing crack would grow to a critical size. The stress contours along the front of planar flaws are also presented for visualization of crack front shape propagation. For a relatively small ratio of the crack depth over shaft diameter, Modes I and II (in-plane) stress intensity factors (SIFs) at the corner points by FEM were observed to be satisfactorily predicted and in good agreements with those by dual boundary element method (DBEM) especially for points away from corner points. Effect of the crack aspect ratio and crack size on the corner point singularity, were noted in this study. The severity of singularity at stepped bars were intensified by the presence of stress concentration caused by geometry irregularity intensity. Mode III SIFs around the corner points by FEA generally diverge from those by DBEM, but for those around deepest points, the SIF calculations by FEA and DBEM showed good agreement for cases of higher crack aspect ratio. On the contrary, although the crack size is relatively small, Mode III SIFs around the corner points by FEA with ultra-fine meshing showed a significant influence of singularity. Hence, it needs more computational development for improvements. This research has demonstrated the viability of using tetrahedral meshing elements in FEM-based software ANSYS to model small cracks and evaluate the SIFs of both non-inclined and inclined semi-elliptical surface cracks in smooth and stepped cylinder bar subjected to axial tension.